2002
DOI: 10.1021/om010938g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Dynamics of [Pd(L−L)H(solv)]+, [Pd(L−L)(CH2CH3)]+, and [Pd(L−L)(C(O)Et)(THF)]+ (L−L = 1,2-(CH2PBut2)2C6H4):  Key Intermediates in the Catalytic Methoxycarbonylation of Ethene to Methylpropanoate

Abstract: A detailed spectroscopic study has allowed the solution structure and dynamic properties of all the intermediates in the Pd-catalyzed methoxycarbonylation of ethene to be established. [Pd(L−L)H(solv)]+ 1 (L−L = 1,2-(CH2PBut 2)2C6H4; solv = MeOH, 1a; PrnOH, 1b; THF, 1c; EtCN, 1d) is static, and the two inequivalent P atoms do not become equivalent through solvent exchange over all the temperatures studied. 2, contains a strong β-agostic C−H interaction which is remarkably stable and is not displaced even in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
89
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 23 publications
9
89
0
Order By: Relevance
“…Van Leeuwen and co-workers gave evidence that the alcoholysis is the ratedetermining step of the alkoxycarbonylation, 133 which was suspected by Heaton. 134 The authors also showed well that the pressure of carbon monoxide does not have any influence on the rate of the alcoholysis. 133…”
Section: Alkoxycarbonylationmentioning
confidence: 87%
“…Van Leeuwen and co-workers gave evidence that the alcoholysis is the ratedetermining step of the alkoxycarbonylation, 133 which was suspected by Heaton. 134 The authors also showed well that the pressure of carbon monoxide does not have any influence on the rate of the alcoholysis. 133…”
Section: Alkoxycarbonylationmentioning
confidence: 87%
“…Monocarbonylated products form through the so called ''hydride'' mechanism, which involves the insertion of the olefin into a Pd-H bond with formation of a Pd-alkyl bond, followed by the insertion of CO into the Pd-alkyl intermediate with formation of a Pd-acyl species, which undergoes alcoholysis or hydrolysis to the ester or the acid with reformation of the Pd-H species starting the catalytic cycle [8][9][10][11]. DEK forms when the insertion of a second molecule of ethene into the Pd-acyl bond occurs with formation of a Pd-alkylacyl intermediate, followed by protonolysis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…C 3 -bridged diphenylphosphine of the type reported on the title, or other diaryl analogues, for example with ortho-methoxy substituents on the phenyl rings, are highly active in the copolymerization process [17], whereas bulkier diphosphines such as t-BuP(CH 2 ) 3 PBu-t or 1,2-bis[(di-tertbutyl)phosphinomethyl]benzene are very active and selective in promoting the methoxycarbonylation to MP [8][9][10][11]17]. That steric bulk plays a role of paramount importance in controlling the selectivity of the reaction is also well illustrated by the results obtained using cationic Pd(II) complexes of 1,1 0 -bis(dialkylphosphino) ferrocene ligand, as when alkyl = methyl the catalyst is very active in promoting high molecular weight PK, whereas when alkyl = ethyl lower molecular weight PK are obtained, and when alkyl = i-propyl the products are MP and DEK [18].…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, and taking note of the bimetallic systems mentioned above, the methoxycarbonylation reaction of styrene and 1-pentene was performed with Al(OTf) 3 as a cocatalyst in place of the more usual Brønsted acid promoters. To our knowledge, it is the first case of a strong, stable, recyclable [12] Lewis acid being used as the cocatalyst in the methoxycarbonylation reaction, and we present the observed rate enhancements over the benchmark Brønsted acids and the formation of stable catalyst systems.…”
mentioning
confidence: 99%